Upaya Peningkatan Hasil Belajar Siswa Dengan Permainan Teka Teki Silang Pada Kd Kebijakan Moneter Dan Fiskal Kls XI IPS MAN 3 Kota Pekanbaru - Putrielis, Ekwanis (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the extent to which the use of crossword puzzles can improve student learning outcomes at KLS XI MAN 3 Pekanbaru on monetary and fiscal policy. This research uses the action research method. The population of this study were 24 class XI IPS 2 students with a sample of all students. This research was conducted in 2 cycles. In cycle 1 the crossword puzzle game has not been used, so it can be seen that the student learning outcomes are unsatisfactory. Then in cycle 2, the crossword game was used. It was seen that there was an increase in student learning outcomes, namely as many as 24 students were able to solve the questions correctly and get scores above the KKM. Then learning was carried out in cycle 2, the steps and planning were carried out the same as cycle 1. The results obtained in cycle 2 were 24 students who were able to complete questions about monetary and fiscal policy and obtained scores above the KKM. From the results of the above research it can be concluded that learning by using crossword puzzles can improve student learning outcomes in KLS XI IPS 2. For this reason, it is expected that teachers are able to carry out learning with various models that are in accordance with the characteristics of learning material.